The Effect Of Human Relations, Work Discipline, And Motivation On Employee Job Satisfaction - Indrasuari, Ni Putu Diah; Maitri, Wayan Sri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the effects of motivation, work discipline, and interpersonal relationships on employee job satisfaction at PT Enggang Angkasa Sarana, a Bali-based company that provides aircraft maintenance and operating support. Enhancing job happiness is essential for raising employee commitment, performance, and organizational stability. To improve comprehension, the study combined qualitative data with a quantitative methodology. Since a saturation sample technique was used, all 95 permanent employees were included in the population and could participate as respondents. SPSS was used for data analysis after structured questionnaires were used to collect the data. All variables were shown to be valid and reliable by instrument testing. Traditional assumption tests were used in multiple linear regression analysis to confirm that the data met the requirements for linearity, multicollinearity, heteroscedasticity, and normality. The results show that motivation, work discipline, and human interactions all significantly and favorably affect employee job satisfaction, both separately and collectively. Motivation was found to have the strongest influence, followed by work discipline and human relations. These findings suggest that improving interpersonal relationships, enforcing consistent discipline, and strengthening motivation through recognition and development opportunities are essential strategies for enhancing job satisfaction and supporting optimal employee performance at PT Enggang Angkasa Sarana.